Comparing the Effects of Lavender Oil and Olive Oil Massage on Pain due to Muscular Cramp during Hemodialysis - Asad Imani; Mohsen Saeedi abo-; Mohammad Alidadi; Elham Shafiei (College of Pharmacy University of Baghdad, 2021)
Background: Pain due to muscular cramp during hemodialysis is one of the most common problems experienced by patient undergoing hemodialysis, and is associated with poor outcomes of patients. The main aim of this study was to comparing the effects of lavender oil and olive oil massage on Pain due to muscular cramp during hemodialysis. Methods: In this random clinical trial, 60 hemodialysis patients were enrolled randomly and allocated to two groups with 30 members in Lordegan and Brojen hospitals, Shahrekord, Iran. The intervention included flora massage on the lower leg muscles so that the first group received olive oil massage (10 drops) and the second group received lavender oil massage (10 drops) for four weeks. After a tow week washout period, the groups were interchanged. The collected data was analyzed in SPSS (v.22) using repeated measure ANOVA and paired t-test. Findings: Pain due to muscular cramp in the lavender group was significantly less than that of the olive oil group in the 2nd (p<0.001), 3rd (p<0.001), and 4th (P<0.019) weeks of intervention. Conclusion: Pain due to muscular cramp in hemodialysis patients can be attenuated with lower leg massage using olive oil and lavender oil. Lavender oil was more effective than olive oil.